MAIN DIRECTIONS OF STATE SUPPORT FOR ECOLOGIZATION OF AGRICULTURE - Burliai , A.P.; Revutska , А.О. (The actual problems of regional economy development, 2020)
The ecologization of agricultural production in the modern world has become one of the urgent problems of society, along with the problem of food security. The article is focused on studying state support for ecologization of agriculture. It is established that the ecologization of agriculture is the primary task of the state to bring agricultural production in line with modern requirements for quality and safety. State support for the ecologization of domestic agriculture is currently at an early level. The experience of organic agriculture in the developed countries of the world demonstrates the need for the state to implement various institutional and organizational and economic measures, as well as the widespread use of financial instruments of state regulation. We propose to systematize the tools of state support for the greening of the agricultural sector of the economy by the following groups: direct state support (subsidies, grants, soft loans, etc.); indirect state support (research, consulting and information services, laboratory research, etc.); formation of appropriate institutional support (certification of production and products; compliance with the requirements for the presence of nitrates in products, the use of pesticides, agrochemicals, fertilizers and GMOs, waste disposal). It is proved that an extremely important financial instrument of state support for the ecologization of the agricultural sector of the economy is the preservation of the "green tariff" for bioenergy producers from alternative sources. Proposals for state support of agriculture in the direction of ecologization the industry have been developed.